Monomer reactivity ratios of the 2-(3-mesityl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate and styrene system from 1H NMR - Erol, I; Soykan, C; Ahmedzade, M (John Wiley & Sons Inc, 2002)
2-(3-Mesityl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate (MCHEMA) was prepared from the reaction of methacrylic acid with the oxirane compound obtained from the chlorhydrin formed in the cyclization of 1-chloro-2,3-epoxy-5-methyl-5-hexene. Copolymers of MCHEMA and styrene were prepared in 1,4-dioxane solution at 60 degreesC using 2,2'-azobisisobutyronitrile as the initiator. They were characterized by IR, H-1 NMR, and C-13 NMR spectra. Their compositions were determined by the H-1 NMR technique. The monomer reactivity ratios were determined by the Fineman-Ross, Kelen, Tudos, and Yezrielev-Brokhina-Roskin method. Thermogravimetric analysis of the copolymers was carried out under a nitrogen atmosphere. The glass-transition temperature of the copolymers as determined by differential scanning calorimetry agreed with the Flory-Fox relationship. (C) 2002 Wiley Periodicals, Inc.
Keywords: hydroxyethyl methacrylate; styrene; copolymer; reactivity ratios; radical polymerization; polystyrene; copolymerization